Safety of ninety-minute daratumumab infusion. (July 2021) - Lombardi, Jeffrey; Boulin, Mathieu; Devaux, Madeline; Cransac, Amélie; Pistre, Pauline; Pernot, Corinne; Payssot, Alexandre; Lafon, Ingrid; Caillot, Denis; Gueneau, Pauline
Purpose: Daratumumab is the first anti-CD38 monoclonal antibody of the class approved for recurrent and refractory multiple myeloma. Grade 3 and 4 Infusion-Related Reactions (IRRs) are frequent during the first and second infusions. Due to the risks associated with severe IRRs, daratumumab is systematically administered over a period of 3.5 hours. The main objective of this study was to evaluate the safety of a 90-minute daratumumab infusion from the third infusion. Patients and methods: All patients who had received two or more doses of daratumumab in monotherapy or in combination with standard infusion rates were included. We excluded patients enrolled in clinical trials. For the rapid infusion protocol, 20% of the dose was administered over 30 minutes and the remaining 80% over 60 minutes. Results: From April 1 to May 31, 2019, 25 patients received 53 90-minute infusions of daratumumab. Premedication included corticosteroids, antipyretics, antihistamines, and if necessary a leukotriene receptor antagonist. No grade 3 or grade 4 IRRs were observed. Conclusion: From the third infusion, we found that a rapid administration of daratumumab (90 vs 210 minutes) was well tolerated and safe. It would be interesting to test this regimen from the second infusion.